Pengaruh Resonator Terhadap Bunyi Slenthem Berdasarkan Sound Envelope: Agung Ardiansyah, Lila Yuwana, Suyatno, Didiek Basuki Rahmat, Susilo Indrawati, Gontjang Prajitno - Agung Ardiansyah, Agung Ardiansyah; Lila Yuwana, Lila Yuwana; Suyatno, Suyatno; Didiek Basuki Rachmad, Didiek Basuki Rachmad; Susilo Indrawati, Susilo Indrawati; Gontjang Prajitno, Gontjang Prajitno (Jurnal Fisika dan Aplikasinya, 2025)
Researching of resonator’s effect towards slenthem sound based on sound envelope has been conducted. The purpose of this research is to investigate gamelan slenthem characteristic based on frequency of tone 3 and sound envelope of that tone. Measurements were taken at tone 3 which affect on each resonator slenthem itself based on each variation of resonator’s frequency. Then measurements towards sound envelope. From the result of sound envelope obtained resonator variation with 1 the fastest time resonator on 2nd resonator at 5,8 seconds, while the longest time resonator on 2nd resonator at 10,6 seconds. Without 1 resonator with the fastest time is 4th without resonator at 23,3 seconds, while the longest time is 3rd without resonator at 30,4 seconds.